A novel comparative study of modified carriers in moving bed biofilm reactor for the treatment of wastewater: Process optimization and kinetic study - Sonwani R.K.; Swain G.; Giri B.S.; Singh R.S.; Rai B.N. (My University, 2025)
In this work, modified plastic carriers; polypropylene (PP), low-density polyethylene- polypropylene (LDPE-PP), and polyurethane foam-polypropylene (PUF-PP) were developed and used in moving bed bioreactor (MBBR) for the wastewater treatment containing naphthalene. To optimized the process parameters using response surface methodology (RSM), two numerical variables; pH (5.0–9.0) and hydraulic retention time (HRT) (1.0–5.0 day) along with the type of carriers (PP, LDPE-PP, and PUF-PP) were selected as a categorical factor. At 7.0 pH and 5 days HRT, maximum removal efficiencies were observed to be 72.4, 84.4, and 90.2% for MBBR packed with PP, LDPE-PP, and PUF-PP carriers, respectively. Gas chromatography–mass spectrometry (GC–MS) analysis reveals catechol and 2-naphthol were observed as intermediate metabolites for naphthalene degradation. Modified Stover–Kincannon model was applied for biodegradation kinetic and constants were observed as Umax: 0.476, 0.666, and 0.769 g/L.day and KB: 0.565, 0.755, and 0.874 g/L.day for PP, LDPE-PP, PUF-PP, respectively. © 2019